Nurse‐rated good death of Chinese terminally ill patients with cancer: A cross‐sectional study. (21st August 2019) - Yang, Hong; Lu, Yuhan; Hou, Xiaoting; Guo, Renxiu; Wang, Yun; Liu, Li; Gu, Yirong; Sun, Hongyu
Abstract: Objective: To explore the good death of terminally ill patients with cancer rated by nurses and identify associated factors in the context of Chinese culture. Methods: We conducted a cross‐sectional, anonymous questionnaire survey. Totally, convenience samples of 122 nurses in charge of 258 patients during their dying period were investigated. The questionnaire consisted nurses' information including demographics and the experience in palliative care, patients' demographic information and disease characteristics, and Good Death Inventory (GDI). Results: Two hundred and fifty‐eight (98.10%) analysable questionnaires were obtained. The total good death score was (245.40 ± 36.91), and the last three were "Independence" (7.34 ± 4.26), "Physical and psychological comfort" (8.12 ± 4.70) and "Religious and spiritual comfort" (8.44 ± 4.55); the first three were "Being respected as an individual" (18.31 ± 2.90), "Good relationship with medical staff" (18.26 ± 2.37) and "Natural death" (18.16 ± 3.22). The unit type, treatment patients received during their last 3 months and nurse's training experience in palliative care were associated factors of good death ( R 2  = 0.135, F  = 9.160, p  < .001). Conclusion: The good death status of terminally ill cancer patients is poor. It's urgent to promote palliative care and strengthen the training about the knowledge and skills to improve the quality of life of the patients, so as to achieve the goal of good death.